A novel mosaic NSD1 intragenic deletion in a patient with an atypical phenotype12. Issue 3 (22nd January 2013) - Castronovo, Chiara; Rusconi, Daniela; Crippa, Milena; Giardino, Daniela; Gervasini, Cristina; Milani, Donatella; Cereda, Anna; Larizza, Lidia; Selicorni, Angelo; Finelli, Palma
Abstract Sotos syndrome, which is characterized by overgrowth, macrocephaly, distinctive facial features, and developmental delay, arises from mutations and deletions of the NSD1 gene at 5q35.3. Sixteen NSD1 intragenic deletions (including one in a mosaic condition) and one partial duplication have been reported in patients with Sotos syndrome. Here, we describe a boy aged 4 years and 10 months that showed facial dysmorphism (including frontal bossing, widely spaced eyes, deeply set eyes, a wide nasal bridge, anteverted nares, and a wide mouth), normal growth, and a psychomotor delay. High‐resolution array comparative genomic hybridization (CGH) analysis identified a mosaic heterozygous intragenic NSD1 deletion of 38 kb, which included part of intron 2 and the entire exon 3, and led to NSD1 haploinsufficiency. The deletion somatic mosaicism was subsequently confirmed by fluorescence in situ hybridization (FISH) analysis using fosmid clones. This patient presents the most atypical phenotype thus far associated with NSD1 haploinsufficiency. It is possible that this atypical phenotype may have resulted from the somatic mosaicism of the NSD1 defect. Our study confirms the usefulness of array CGH for increasing the detection rate of NSD1 abnormalities and for diagnosing syndromic patients that do not present an easily recognized phenotype. © 2013 Wiley Periodicals, Inc.